Optimal economic strategy for the multiperiod design and long-term operation of natural gas combined cycle power plants - Godoy, Ezequiel (2012)
Optimal power plant designs are achieved by means of a proposed multiperiod non-linear programming formulation that utilizes the net present value as objective function, while construction, operation and dismantling of the generation facility are accounted for. In addition, optimal operative characteristics are also established for each operative time period, in a way that the system constraints are always satisfied. Based on the life cycle oriented economic optimal characteristics, a reduced model is proposed as strategy for simplifying the resolution of the rigorous multiperiod model. Trends in the system behavior are identified, enabling the reduction of the multiperiod formulation into a system of non-linear equations plus additional constraints, which allows easily computing accurate estimations of the optimal values of the design variables as well as the time-dependent operative variables.